ANALISIS SUMBER BAHAYA DAN POTENSI BAHAYA PADA UNIT PROCESSING DI PT. PP LONDON SUMATRA INDONESIA TBK - Satwanto, Gia Budi; Heriyono, Muhamad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Industrial activities are inseparable from sources of danger, potential risks of workplace accidents and occupational diseases. No matter how small an accident or occupational disease is, it can have a relatively large impact on a company. Likewise, a manufacturing industry that involves humans in the production process can involve the risk of workplace accidents. Modern technology, changes in work forms, organizations, and production systems place high demands on workforce. To address problems or sources of danger, implementing improvements in occupational safety and health performance is a must. To identify sources of danger and potential hazards in the Processing Unit at PT. PP London Sumatra Indonesia Tbk., the type of research conducted was descriptive research with direct observation using a checklist. Hazard sources are found in almost all processing units, and potential hazards are also present in almost all processing units.Keywords: source of hazard, potensial hazard, processing units